Show that "¬p Λ q is logically equivalent to p → ¬q" . I'm not sure if the conditional identity is correct, but what I did was I negated the whole second condition and it immediately became equal to the first? Please help and if possible, show steps or what laws I have to use. Thank you.
With simple expressions like these, the easiest proof is to make a truth table...unless it is specifically prohibited in the question.
Also, there are precedence in the logical operators, just like + - * ÷.
The ¬ operator (which I write as ~ for simplicity) has the highest priority, in this order.
There the first expression is interpreted as (~p)∧q which is not an identity to p->~q.
However, writing the first expression as ~(p∧q) will give a truth table of
identical to that of
hence the identity
~(p∧q) ≡ p->~q
@MathMate Thank you so much! No wonder I was going nowhere even when I did the truth table, I had a mistake in translating the proposition. Thanks again.posted by Luke
You're welcome! :)